PENGARUH CASH TURN OVER, ACCOUNT RECEIVABLE TURN OVER DAN INVENTORY TURN OVER TERHADAP PROFITABILITAS PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BEI TAHUN 2014-2017 - Syavira Fitriyanti; Harsi Romli; Fakhry Zamzam (Program Magister Manajemen Indo Global Mandiri University, 2021)
The aim of this research is to know the influence of independent variables CTO, ARTO, and ITO to dependent variable profitability (ROA), either partially or simultaneously. The object of this research are mining companies listed in Indonesian stock exchange period 2014-2017. Samples for this research consists of 5 companies, purposive sampling method used in this research. The analysis technique used multiple linear regression. The result shows that cash turnover give negative and significant influence to profitablity (ROA), account receivable turnover give positive and significant influence to profitabilty (ROA), , inventory turnover give positive and significant influence to profitability (ROA), and CTO, ARTO, and ITO together have a positive and significant effect on Profitability (ROA) at PT. Timah, Tbk, PT. Bukit Asam, Tbk, PT. Antam, Tbk, PT. Bumi Resources, Tbk, and PT. Indo Tambang Megah, Tbk 2014-2018 quarterly period based on the regression equation above, it can be analyzed that the effect of each independent variable on the dependent. The average value of the (random error component) is 0.248710. the R-Squared value is 0.729426 (72.94%), this indicates that all independent variables effect the dependent variable by 72.94 percent and the rest is influenced by variable outside the model. Overall the independent variables have a significant effect on the independent variables with a prob (F-Statistic) value of 0.000057, less than 0.05.